Estrogen receptor expression in type 1 endometrial cancer and its association with lymphovascular space invasion - Fidiawati, Wiwit Ade; Andrijono; Siregar, Nurjati Chairani; Prihartono, Joedo; Purwoto, Gatot; Hellyanti, Tantri (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND Endometrial cancer (EC) ranks sixth in female genital malignancy and originates in the endometrial lining. Estrogen receptor (ER) expression is important in EC prognosis and recurrence, influenced by the presence of lymphovascular space invasion (LVSI). This study aimed to determine the association between ER expression and LVSI in type 1 EC. METHODS A retrospective analysis was conducted on 135 patients with type 1 EC who underwent surgery at the Cipto Mangunkusumo Hospital, Jakarta, Indonesia, between January 2012 and December 2022. Immunohistochemistry (IHC) with ER antibodies was performed on all samples in April 2023. ER expression was evaluated using the Allred scoring system, and its association between ER expression (percentage and intensity stain) and LSVI was statistically analyzed. RESULTS Of 135 samples, 44 (32.6%) were LVSI-positive. No significant association was found between IHC percentage stain and LVSI (p = 0.994). However, a significant association was found between IHC stain intensity and LVSI-positive in patients with type 1 EC (p = 0.022). ER intensity score 2 had a higher LVSI risk compared to score 1 and score 3 (from 51%, 26%, and 26%, respectively). CONCLUSIONS ER expression is associated with LVSI of type 1 EC. While IHC stain percentage showed no correlation with LVSI, stain intensity was significantly linked to LVSI-positive in patients with type 1 EC. Regular assessment of ER expression can provide significant prognostic information, support hormonal therapy, and identifying clinical characteristics of tumors.